Tri Hita Karana-Based CSR: How Hotel Relates to Community during the Covid-19 Pandemic - Ni Wayan Budi Purnama Dewi; Ni Made Ernawati; I Gede Mudana; Anak Agung Ayu Ngurah Harmini; Ni Putu Somawati (Catuspata Press, 2022)
Purpose: This study aims to examine the implementation and develop a corporate social responsibility (CSR) model based on the Tri Hita Karana culture during the Covid-19 pandemic at the Ritz-Carlton Bali, Indonesia. Research methods: Data collection techniques are observation, interviews and documentation studies. Data analysis was carried out with the stages of data reduction, data presentation, and drawing conclusions. Findings: The Ritz-Carlton in Bali carried out CSR activities based on the Tri Hita Karana culture during the COVID-19 pandemic on a limited basis. Then the model development results in: CSR activities are more focused on efforts to provide assistance to fellow humans (Human), CSR activities are carried out to protect nature (Nature), CSR activities need to consider matters related to business, CSR activities respect the culture of the local community (Culture) . Implication: This research can be used as material for consideration and evaluation of hotels related to CSR activities based on the Tri Hita Karana culture during the Covid-19 pandemic.